2012
DOI: 10.1158/1055-9965.epi-11-1178
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Nicotine and Carcinogens among Southwestern Alaskan Native Cigarette Smokers and Smokeless Tobacco Users

Abstract: Background The prevalence of tobacco use, both cigarette smoking and smokeless, including iqmik (homemade smokeless tobacco prepared with dried tobacco leaves mixed with alkaline ash), and of tobacco-related cancer is high in Alaskan Native people (AN). To investigate possible mechanisms of increased cancer risk we studied levels of nicotine and tobacco-specific nitrosamines (TSNA) in tobacco products and biomarkers of tobacco toxicant exposure in Southwestern AN people. Methods Participants included 163 cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
0
25
1
1
Order By: Relevance
“…However, our results are consistent with a prior study by Benowitz et al, which revealed plasma cotinine and urine nicotine levels in AN men and (nonpregnant) women were significantly higher among iqmik users compared to cigarette and other ST users. 12 Plasma cotinine and urine nicotine levels were comparable between groups.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, our results are consistent with a prior study by Benowitz et al, which revealed plasma cotinine and urine nicotine levels in AN men and (nonpregnant) women were significantly higher among iqmik users compared to cigarette and other ST users. 12 Plasma cotinine and urine nicotine levels were comparable between groups.…”
Section: Discussionmentioning
confidence: 85%
“…Cotinine, which has a longer half-life than nicotine, is a well-established biomarker for tobacco exposure and is easily measured in urine. 12 NNAL, the tobacco-specific carcinogenic metabolite of NNK, has an even longer half-life (10-16 days) and can also be measured in urine. 12,13,15 We sought to enroll a convenience sample of 165 pregnant women (55 smokers, 55 ST [commercial ST and iqmik] users, and 55 non-[tobacco] users) seeking prenatal care at SCF outpatient clinics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine and carcinogen bioavailability appear to vary dramatically across these tobacco products [49]. This study is limited to assessment of cigarettes, commercial ST and iqmik , mainly due to the minimal use of pipe or cigar smoking in these regions and by the collection of these baseline data well before the widespread use of e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that dual- and multi-product tobacco users experience lower cessation rates [17,18], possibly due to greater cotinine and dependence levels [50]. On average, AN smokers living in Bristol Bay smoke about half as many cigarettes (7.8) per day [42] as US smokers (14.2) [51], but demonstrate similar plasma cotinine levels (170 ng/mL and 200 ng/mL, respectively), suggesting altered nicotine metabolism [49,52]. These changes in nicotine pharmacokinetics imply the need for a increased dosing of nicotine replacement therapy to aid in smoking cessation, a need that may extend to other AN populations, such as those in the Y-K or Norton Sound regions.…”
Section: Discussionmentioning
confidence: 99%